(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Diabetic foot ulcer is one of the common complications experienced by patients with diabetes mellitus (DM). Loss of sensation in the distal part of the foot due to peripheral neuropathy is one of the triggering factors for the occurrence of ulcers. If not treated promptly, ulcers may progress into severe infections that can lead to amputation. Therefore, patients with DM need to be aware of early signs that may cause the development of ulcers. Independent assessment and care of diabetic feet should be carried out by patients themselves to optimally prevent diabetes complications; hence, guidelines or protocols are needed as a reference for patients in performing the steps of foot assessment and care to prevent diabetic foot ulcers. This activity aimed to train the community, particularly in Sungai Ambangah Village, Kubu Raya, West Kalimantan, in applying the guidelines for diabetic foot prevention, which was conducted on December 29, 2024. The implementation method included several stages: a survey of the target group, preparation of facilities and infrastructure, implementation of the activity, and evaluation. The results showed that the majority of participants were between 46–55 years old (18 participants, 60%), female (17 participants, 56.67%), had suffered from DM for more than 5 years (21 participants, 70%), and achieved an average difference score of 21.13 in their ability to apply the guidelines for diabetic foot prevention after the workshop. The average N-Gain Score was 57.37. Since the average N-Gain Score falls within the range of 56–75, this indicates that the workshop on the implementation of diabetic foot prevention guidelines was effective in improving participants’ ability to perform diabetic foot assessment and care.